2019
DOI: 10.1158/1538-7445.am2019-943
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 943: Filtering out self-like neoantigens improves immune response to cancer vaccines

Abstract: Clinical studies have highlighted the potential of precision cancer immunotherapy to effectively control the tumor of patients across cancer indications. However, recent studies showcase the difficulty of establishing robust CD8 and CD4 T cell responses. We hypothesize that poor cancer vaccine performance may be due in part to the inadvertent inclusion of suppressive T cell neo-epitopes in neoantigen vaccines that may be recognized by regulatory T cells (Tregs). To test this hypothesis, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This led to the concept of 'immune camouflage' and suggested that pathogens may evolve to escape immune responses. Furthermore, the epitopes that were the target of the pathogen camouflage epitope appeared to be extensively cross-conserved within the human genome, a feature of T cell epitopes that induced active tolerance (55, 56). The tool has been used to identify Treg epitopes in human pathogens such as Hepatitis C virus (55), and avian influenza virus H7N9 (57).…”
Section: Integrating Assessment Of Tolerogenic Epitopesmentioning
confidence: 99%
“…This led to the concept of 'immune camouflage' and suggested that pathogens may evolve to escape immune responses. Furthermore, the epitopes that were the target of the pathogen camouflage epitope appeared to be extensively cross-conserved within the human genome, a feature of T cell epitopes that induced active tolerance (55, 56). The tool has been used to identify Treg epitopes in human pathogens such as Hepatitis C virus (55), and avian influenza virus H7N9 (57).…”
Section: Integrating Assessment Of Tolerogenic Epitopesmentioning
confidence: 99%
“…Optimal neoantigens may be defined by several factors including the level of neoantigen gene expression, the processing of peptide fragments, the binding affinity of neoantigen peptide fragments to HLA, successful presentation on the surface of the cell, and the phenotype of the immune cell that responds to the neoantigen. The exclusion of potential regulatory T cell (Treg) epitopes in the tumor mutanome has been one focus of our cancer vaccine development program 8 . Other groups have also reported that tolerizing epitopes may arise during the mutational process, and that these suppressive epitopes have a deleterious effect on cancer vaccine efficacy 9 .…”
Section: Introductionmentioning
confidence: 99%
“…This has been observed in the context of infectious disease antigens, where pathogen-derived epitopes presenting a TCR "face" homologous to self-derived epitopes elicited CD4 + CD25 + FoxP3 + (regulatory) T cell (Treg) responses 10 , 11 , which in turn led to the suppression of effector immune responses against co-administered epitopes 11 . Removal of self-like epitopes from vaccine formulations has shown to increase immunogenicity of H7N9 influenza and CT26 vaccines 8 , 12 and protection against lethal H7N9 challenges 13 . Preliminary work from our group in oncology suggests these "self-like" inhibitory neoepitopes also exist in mutated antigens derived from the murine colon carcinoma CT26 cell line 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation